Valerius Flaccus, Argonautica, Book V : a commentary - Wijsman, H. J. W. (Mnemosyne, Supplements, 1996)
The book contains a commentary on Book V of the Argonautica of Valerius Flaccus, paying attention to linguistic, philological and literary aspects. Line by line the words and phrases chosen, sources used and literary models are treated. The last commentary on all eight books of the Argonautica appeared a century ago (Langen 1896), so there is ample room to apply new views in Latin linguistics and concepts of literature. A small number of textual variants is supported.